Creating Patient and Family Education Web Sites: Assuring Accessibility and Usability Standards - YADRICH, DONNA MACAN (2012)
This article gives details about the methods and processes used to ensure that usability and accessibility were achieved during development of the Home Parenteral Nutrition Family Caregivers Web site, an evidence-based health education Web site for the family members and caregivers of chronically ill patients. This article addresses comprehensive definitions of usability and accessibility and illustrates Web site development according to Section 508 standards and the national Health and Human Services’ Research-Based Web Design and Usability Guidelines requirements.